Photocatalytic oxidation of air toxics via visible light irradiation and nano-photocatalysts - Ullah, Ruh (Curtin University, 2012)
This thesis explores synthesis of various types of metal oxide nanoparticles through a wet-chemical synthesis route. The materials were used for photocatalytic oxidation of gaseous toluene irradiated with UV, artificial solar light, and pure visible light. Tantalum based compounds like BiTaO4: La, BiNbO4: Ga and Ta2O5 have shown better performance than a commercial TiO2 under UV and solar light. Ta2O5 and nitrogen doped Ta2O5 have shown excellent performance for toluene oxidation with solar and visible light.